The LiberAction Project: Implementation of a Pediatric Liberation Bundle to Screen Delirium, Reduce Benzodiazepine Sedation, and Provide Early Mobilization in a Human Resource-Limited Pediatric Intensive Care Unit - Di Nardo, Matteo; Boldrini, Francesca; Broccati, Francesca; Cancani, Federica; Satta, Tiziana; Stoppa, Francesca; Genuini, Leonardo; Zampini, Giorgio; Perdichizzi, Salvatore; Bottari, Gabriella; Fischer, Maximilian; Gawronski, Orsola; et al. (Frontiers in Pediatrics, 2021)
Background: Delirium, bed immobilization and heavy sedation are among the major contributors of pediatric post-intensive care syndrome. Recently, the Society of Critical Care Medicine has proposed clinical interventions to minimize these morbidities, but, unfortunately, these interventions require important structural and economical interventions which prevent their use in limited resource pediatric intensive care (PICU) units. Aim: To evaluate the feasibility and safety of a PICU bundle implementation prioritizing delirium screening and treatment, early mobilization (<72 hour from PICU admission) and benzodiazepine-limited sedation in a limited resource PICU. Methods: This project was structured in a pre-implementation period (15th November 2019-30th June 2020) and a post-implementation period (1st July 2020-31st December 2020). During the pre-implementation period, a retrospective cohort of patients admitted to PICU for more than 72 hours served as a control group. A prospective cohort of patients admitted in PICU for more than 72 hours served as intervention group in the post-implementation period. During the pre-implementation period, a rehabilitation program including delirium screening and treatment, early mobilization and benzodiazepine-sparing sedation was developed and all PICU staff were trained. During the post-implementation period, delirium screening was implemented. Early mobilization was performed using a structured tiered protocol and a new sedation protocol, limiting the use of benzodiazepine, was adopted. Results: One hundred and thirty-seven children were enrolled in the pre-implementation period and 88 in the post-implementation period. Adherence to delirium screening, benzodiazepine-limited sedation and early mobilization was 90.91%, 81.13% and 70.45%, respectively. Incidence of delirium was 25%. The median cumulative dose of benzodiazepine (midazolam and lorazepam) corrected for the total number of sedation days was significantly lower in the post-implementation period compared with the pre-implementation period: [0.83(IQR:0.53-1.31) vs 0.74(IQR: 0.55-1.16),p=0.0001]. The median number of mobilizations per patient and their duration significantly increased in the post-implementation period [3.50(IQR: 3.0-4.0) vs 7.00(IQR: 3.0-12.0);p=0.004 and 4 minutes(IQR:3.50-4.50) vs 5.50 minutes(IQR: 5.25-6.5);p<0.0001,respectively]. No adverse events related to early mobilization were reported in both periods. Conclusion: This study showed that the implementation of a PICU liberation bundle prioritizing delirium screening and treatment, benzodiazepine-limited sedation and early mobilization was feasible and safe even in a limited resource PICU.